Progressive tool wear in machining biomedical alloy using uncoated and titanium diboride coated tungsten carbide tools - Mohd Hafizu, Zakaria (2019)
In the industry of cobalt chromium (CoCr) alloys processing, hard metals consist of high fraction of tungsten carbide (WC) or carbon boron nitride (CBN) grains embedded in a relatively soft and tough cobalt (Co) binder matrix are widely used for the cutting materials and wear resistant applications. Albeit gaining popularities as advanced materials in various aerospace, automotive and medical applications; owe to their superior properties such as good strength-to-weight ratio, and biomedical applications due to high corrosion resistance and biocompatibility, machinability of these alloys has been proven difficult to cut. Major factor reducing the machinability of CoCr alloys is the very strong chemical affinity between the Cr and Co binder in the tungsten carbide tool which encourages tendency of weldment of the work material to the cutting tool during machining, resulting notch, chipping and premature tool failure. This study was conducted to investigate the progressive tool wear in machining cobalt chromium alloys and evaluate the machining performance in terms of their tool life, wear mechanism, tool cutting temperature and surface roughness of the workpiece in dry machining using uncoated and titanium diboride (TiB2) coated tools. To investigate the gradual generation of wear of the cutting tools, it is important prior cutting trials to evaluate the characteristics of the tool materials using physical (i.e. density and surface roughness of the tools with and without coating), and mechanical (i.e. micro hardness and heat distribution inside the tool bulk) tests. Then for the cutting trials cutting parameters of the CNC turning process were kept constant; i.e. cutting speed (Vc): 60 m/min, feed rate (f): 0.1 mm/rev, and depth of cut (ap): 0.25 mm with original workpiece diameter 50 mm. The tool life was determined based on standard ISO3685:1993. The wear mechanism, wear generation, tool temperature and surface roughness were measured using scanning electron microscope, portable microscope, K-type thermocouple and Marsurf-PS1 device, respectively. The results of cutting tool characterisation indicate that the single layer TiB2 offers high hardness which can intensify wear resistance of WC tool against premature tool failure. Assessing the machining performance of TiB2 coated tool against uncoated tool, presented that tool life of over five minutes can be achieved with both tools. Further investigation on the rate of tool wear though showed that uncoated tool undergone higher wear rate of 13.7 % than TiB2 coated tool. The phenomenon of tool wear affected surface roughness and wear mechanism as the average surface roughness of coated tool is 0.9 μm and uncoated is 1.4 μm. The same wear mechanism for both cutting tool were observed including adhesion and abrasion. However, based on the energy dispersive x-ray (EDX) elemental analysis, the coating of the cutting tool reduces the weldment of material element which causes adhesion wear mechanism on cutting tool. In conclusion, the improvement of machining performance exhibited by TiB2 coated carbide cutting tool in dry machining of cobalt chromium alloy with 1.38 % percentage difference of flank wear. This has paves a significant step for sustainable manufacturing of high end applications in aerospace, automotive and medical industries. Analytical investigation into the effects of cutting parameters on the machinability of CoCr alloys is recommended to obtain optimum cutting condition for improving economical and quality aspects of machining.